Health beliefs of unmarried adult Saudi individuals toward safe marriage and the role of premarital screening in avoiding consanguinity: a nationwide cross-sectional study - Alwhaibi, Reem M.; Almuwais, Afrah K.; Alotaibi, Madawi; AlTaleb, Hanan M.; Alsamiri, Shatha M.; Khan, Ruqaiyah (Frontiers in Public Health, 2024)
Introduction: Premarital screening (PMS) is an essential global measure that seeks to reduce the occurrence of specific genetic disorders and sexually transmitted diseases common in consanguineous marriages. Due to the lack of a nationwide study, this research was designed to comprehend how unmarried individuals perceive the risks and benefits of PMS.A cross-sectional study was conducted using an online questionnaire distributed through different social media platforms, responses from the native adult population (18-49 years) Saudi Arabia was only included in the study. The questionnaire was based on the Health Belief Model (HBM) to assessing seven different constructs including susceptibility, seriousness, benefits-, barriers-, & cuesto action, self-efficacy, and social acceptance. Data frequency was represented by mean and standard deviation; chi-square and t-tests were conducted for the comparison of independent and dependent variables. A multinomial logistic regression was used to predict factors influencing decisions related to PMS.Results: 1522 participants completed the survey, mostly 18-25 years old and most of them were women. The majority were single with 85 men and 1370 women. Most participants (59.6%) believed their parents were related, while 40.5% did not. 122 respondents reported they had to marry within their tribe. Findings revealed significant correlations among all HBM themes, with varying strengths. Notably, a moderate positive relationship was found between the perception of benefits and cues to action, suggesting that enhancing the perceived benefits of PMS could facilitate safe marriage practices. Multinomial regression analysis revealed that demographic factors and health beliefs significantly influence individuals' intentions and behaviors towards PMS and safe marriage.The study concludes that by identifying and addressing barriers, and promoting positive social acceptance, PMS can significantly contribute to preventing genetic diseases and promoting safe Restricted -‫مقيد‬ marriage practices, although the cross-sectional design limits the establishment of causal relationships and further research is needed.